ACTION GUIDELINES FOR EFFECTIVE MANAGE LABOUR MIGRATION – CASE STUDY FOR ROMANIA - Pasnicu, Daniela (Annals of Spiru Haret University. Economic Series, 2013)
The relationship between migration, growth and development is complex. Moreover, in Romania, relatively little is known about this phenomenon, especially due to the fact that the magnitude of flows of workers is insufficiently determined and structured. This leads to assuming a certain degree of caution when political and institutional implications and alternatives are discussed. To support the effective management of labour migration, this study will analyze migration policies considered barriers against mobility and structural characteristics of migration flows by using databases published by the Italian and Spanish authorities. The paper concludes with action guidelines to maximize the positive and minimize the negative effects of migration for Romania, and implicitly for Romanian citizens.